2015
DOI: 10.15376/biores.10.2.3254-3264
|View full text |Cite
|
Sign up to set email alerts
|

Fire Performance of Si-Al Ultra-Low Density Fiberboards Evaluated by Cone Calorimetry

Abstract: To clarify how the fire resistance of ultra-low density fiberboards (ULDFs) was improved by the Si-Al compounds and to compare the effect of fire resistance between Si-Al compounds and fire retardant (chlorinated paraffin), the fire performance of ULDFs was evaluated by cone calorimetry. Comparing Si-Al compounds to chlorinated paraffin, the heat release rate (HRR), total heat release (THR), mass loss, total smoke release, and off-gases (CO and CO2) release of ULDFs treated with Si-Al compounds significantly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…For example, the char yield of MF at 350 °C and 500 °C increased by 78.31% and 112.78%, respectively, compared with CF. These results indicated that the fire resistance of fiberboards is improved by complex fire-retardants, which improve the protection properties of the residues (Chen et al 2015b(Chen et al , 2016a. …”
Section: Effect Of Temperature On the Char Yield Of Ultra-low Densitymentioning
confidence: 86%
See 2 more Smart Citations
“…For example, the char yield of MF at 350 °C and 500 °C increased by 78.31% and 112.78%, respectively, compared with CF. These results indicated that the fire resistance of fiberboards is improved by complex fire-retardants, which improve the protection properties of the residues (Chen et al 2015b(Chen et al , 2016a. …”
Section: Effect Of Temperature On the Char Yield Of Ultra-low Densitymentioning
confidence: 86%
“…The inorganic film insulates wood against air during combustion (Unger et al 2012;Chen et al 2015b). Potassium carbonate (K2CO3), a component of Si compounds, releases noncombustible gas (CO2) at 400 °C.…”
Section: A B C Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The HRR curves demonstrated a two-peak profile, especially the SF curve, due to the thermo-oxidative decomposition of the char. Furthermore, Si compounds formed a barrier to heat and mass transfer that caused the further decomposition and cracking of the char towards the burned ends where the second peak occurred (Hagen et al 2009;Shabir Mahr et al 2012;Chen et al 2015b). Compared with CF, the HRR profiles of BF, NPF, SF, HF, and MF were reduced.…”
Section: Analysis Of Response Surface and Optimizationmentioning
confidence: 99%
“…Among BF, NPF, SF, and HF, the residual mass of SF (35.49%) was higher by 9.78%, 3.68%, and 14.01% than BF, NPF, and HF, respectively. This result could be ascribed to the inorganic film, which acts as a barrier to fuel transport (Sacristán et al 2010;Chen et al 2015b). In contrast, chlorinated paraffins cannot form a barrier to slow or prevent the release of fuel to the flame front, which corresponded to its high value of HHR and low percentage mass loss (21.48%).…”
Section: Mass Loss Vs Timementioning
confidence: 99%